2019
DOI: 10.1002/hpm.2920
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between health care providers' perceived work climate, organizational commitment, and caring efficacy at pediatric intensive care units, Cairo University

Abstract: Summary Background Healthy work environment has a significant impact on patients, health care workers, and organizations. Objectives In a trial to set up strategies to control stressors and weaknesses in the work environment, the present study took place in pediatric intensive care units (PICUs) to explore the work environment and its impact on the organization commitment and caring efficacy of health care providers. Methods This study is a descriptive cross‐sectional study, conducted over a period of 9 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Our generic model is also supported by Attia et al [43] who compared job performance in nurses and doctors, with the former having better results in terms of job outcomes and job satisfaction. Additionally, in the study by Gostautaite [190] it includes age as a moderator of work outcomes.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Our generic model is also supported by Attia et al [43] who compared job performance in nurses and doctors, with the former having better results in terms of job outcomes and job satisfaction. Additionally, in the study by Gostautaite [190] it includes age as a moderator of work outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…In the development of organizational commitment there are numerous variables that have been found to be related, including demographic variables: age [ 38 , 39 , 40 ], educational level [ 40 , 41 , 42 ], gender [ 39 ], and nationality [ 38 ]. On the other hand, personal variables that enhance organizational commitment include: self-perception of effectiveness [ 43 ] and work ethos [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar finding was reported by Attia et al that nurses had significantly higher work commitment (32±5.1) than doctors (29.8±4.6) in Egypt. 30 These results might encourage rural healthcare organisations to focus more on doctors to enhance their work commitment.…”
Section: Discussionmentioning
confidence: 99%
“…29 Attia et al identified a significant direct correlation between the work commitment of healthcare workers and perceived caring efficacy. 30 Horwitz reported that the affective commitment of physicians was positively related to improving patient safety culture. 31 Two studies in China found that work commitment was significantly and directly inversely associated with the presenteeism of healthcare workers.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%